Lasting impression of violence: Retained bullets and depressive symptoms. Issue 1 (January 2018) - Smith, Randi N.; Seamon, Mark J.; Kumar, Vinayak; Robinson, Andrew; Shults, Justine; Reilly, Patrick M.; Richmond, Therese S.
Abstract: Background: Over 70, 000 nonfatal firearm injuries occur in the US annually, frequently leaving victims injured with retained bullets. The long-term psychological risks associated with retained bullets remains unstudied. By serving as a constant reminder of injury, we hypothesized that the presence of retained bullets after firearm injury is associated with increased PTSD and depression symptom severity. Methods: We conducted a prospective cohort study (2013–2015) of Black male survivors of firearm injury at an urban Level I trauma center. Interviews, questionnaires and validated survey tools for PTSD (PCL-5) and depression (QIDS-SR16 ) to assess severity of symptoms were administered 3 months post-injury. Clinical characteristics and symptom severity scores were compared with respect to retained bullets using Wilcoxon Rank Sum tests and linear regression. Results: Of 139 participants, 101(73%) had retained bullets. The cohort was young (mean age 26 years), educated (82% high school or greater) yet unemployed (53%) and with multiple injuries (median [IQR] no. of GSWs 2 [1–3]). There was no difference in age, education, employment status, number of gunshot wounds, operative procedures, pain, hospital or ICU LOS between groups (p > 0.05). Patients with retained bullets less often rated their health as "very good" or "excellent" (10% vs 29%, p = 0.046). Of those working prior to injury (n = 47), 61% with retained bullets had not returned to work compared to 33% without retained bullets (p = 0.027). No difference in PCL-5 scores [30.9 (SD 18.9) vs 27.9 (SD 18.6), p = 0.470] was observed, but patients with retained bullets had greater mean QIDS-SR16 scores [10.7 (SD 6.2) vs 7.8 (SD 6.1), p = 0.038] than those without. After controlling for injury severity, number of wounds, marital status and education level, multiple linear regression analysis determined that retained bullets (β = 3.52; p = 0.017) were associated with more severe depressive symptoms. Conclusion: Retained bullets are associated with adverse psychological consequences after firearm injury. To improve recovery and to aid in clinical management decisions, clinicians should consider both the psychological and physical effects of retained bullets in survivors of firearm injury.